THE ROLE AND SIGNIFICANCE OF MOBILE APPLICATIONS IN THE EDUCATIONAL SYSTEM - Nurmatov, Ilxom Ismoilovich (Educational Research in Universal Sciences, 2023)
This article analyzes the advantages and disadvantages of mobile applications in the educational system, as well as the technology of e-learning management.